(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, we draw our attention to scientists of the Academy of International Sciences of the Russian Higher School V.E.Shukshunov and V.F. Vzyatyshev. According to them, the primary scientific foundations of the new educational policy should be sought in three spheres: philosophy of education, human and social sciences, and "theory of practice". We will provide more detailed information about them below.